Peritoneal Inclusion Cyst in a Young Patient with a Long Clinical Coarse Dealt as Ascites. - Nobi, Md Ayakub; Reza, Israt Binte; Foysal, Mahamud Riyad; Ahasan, HAM Nazmul (Bangladesh Journal of Medicine, 2024)
Peritoneal inclusion cysts are reactive, fluid filled lesions of the peritoneal lining, mostly affecting women of reproductive age. It commonly occurs with history of previous abdominal surgeries. Paraovarian cysts, hydrosalpinx, cystic mesothelioma, giant intra-abdominal cysts with uncertain origin are usually considered in the differential but ‘may mimic ascites’ when it becomes hugely enlarged. In this case report, we present a 23 -year-old female with no known co-morbidities presented to us with progressive abdominal distention. During excluding causes of abdominal distention, peritoneal cyst was suggested on computed tomography and laparoscopic excision was done. Peritoneal inclusion cyst is a rare entity and quite difficult to diagnose and choose appropriate treatment for individual patient. Bangladesh J Medicine 2025; 36: 60-63